Imperfect information about financial frictions and consequences for the business cycle - Josef Hollmayr; Michael Kühl (Deutsche Bundesbank, 2015)
In this paper, we discuss the consequences of imperfect information about financial frictions on the macroeconomy. We rely on a New Keynesian DSGE model with a banking sector in which we introduce imperfect information about a limited enforcement problem. Bank managers divert resources and can increase the share of diversion. This can only be observed imperfectly by depositors. The ensuing imperfect information generates a higher volatility of the business cycle. Spillovers from the financial sector to the real economy are higher and shocks in general are considerably amplified in the transition period until agents' learning is complete. Volatility and second-order moments also display an amplification under the learning setup compared with the rational expectations framework.
Keywords: E3; E44; G3; 330; DSGE Model; Financial Frictions; Learning